Contribution of recycled moisture to precipitation in oases of arid central Asia: A stable isotope approach. Issue 4 (29th April 2016) - Wang, Shengjie; Zhang, Mingjun; Che, Yanjun; Chen, Fenli; Qiang, Fang
Abstract: Terrestrial moisture contributed by surface evaporation and transpiration, also known as recycled moisture, plays an important role in hydrological processes especially across arid central Asia. The stable hydrogen and oxygen isotopes can be used for water budget analysis to calculate the contribution of recycled moisture to precipitation between two locations along the moisture flow. Based on a three‐component isotopic mixing model, the moisture recycling in oasis stations of arid central Asia during summer months is assessed. At large oases of Urumqi, the proportional contribution of recycled moisture to local precipitation is approximately 16.2%, and the mean proportions of surface evaporation and transpiration are 5.9% ± 1.5% and 10.3% ± 2.2%, respectively. At small oases like Shihezi and Caijiahu the contribution of recycled moisture is less than 5%, and the proportion of surface evaporation is much less than that of transpiration. The vegetative cover in arid central Asia is generally sparse, but the evapotranspiration contribution to precipitation cannot be ignored at the widely distributed oases. The oasis effect shows great variability depending on locations and water availability for evapotranspiration. Key Points: Moisture recycling in oases under an arid climate is assessed using an isotope method Contribution of recycled moisture to precipitation varies from 3.4% to 16.2% in different oases Uncertainty of three‐component isotopic mixing model is discussed